Cross-national equivalence of vocational skills and qualifications - Brockmann, Michaela [Verfasser]; Clarke, Linda [Verfasser]; Winch, Christopher [Verfasser] (My University, 2009)
"The introduction of an European Qualifications Framework is allied with the intention of rendering qualifications comparable and thus increasing the level of transparency and mobility within the European educational and employment system. In terms of specific implementation of the EQF, however, a number of hurdles remain to be overcome. The present paper takes the initial results from comparative case studies as a basis for identifying the barriers of oppurtunities emerging from the endeavours to establish cross-country equivalence of qualifications and skills. Whereas establishing understanding of joint terminologies has a part to play, general national conditions and sector and occupationally specific regulations are also of singnificance." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; T 1.5 International vergleichende Berufsbildungsforschung; Europäischer Qualifikationsrahmen; Qualifikation; Gleichwertigkeit; Fallstudie